TINGKAT SELF-EFFICACY BERHUBUNGAN DENGAN BURNOUT PADA PERAWAT SELAMA PANDEMI CORONA VIRUS DISEASE 2019 - Putri, Ni Kadek Konik Damayanti; Krisnawati, Komang Menik Sri; Utami, Kadek Cahya (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022DO - 10.24843/coping.2022.v10.i05.p04, 2022)
The 2019 Corona Virus Disease pandemic requires the public, especially nurses, to adapt to various changes that can cause stress. Uncontrolled stress can lead to burnout. Burnout can be minimized by having self-confidence to be able to achieve the desired results. This study aims to determine the correlation between the level of self-efficacy and burnout in nurses in the Emergency Installation Unit of the Technical Implementation Unit of the Bali Mandara General Hospital during the 2019 Corona Virus Disease pandemic. The method that used in this research is descriptive correlation with cross sectional design. The number of samples in this study were 35 nurses using a total sampling technique. Pearson Product Moment was used to analyzed data. Most of the respondents in this study had a moderate level of self-efficacy (74,3%) and a moderate level of burnout (97,1%). The results of this study obtained a p value of 0,000 (p < 0,05). The correlation coefficient value obtained at -0,587 showing negative and strong correlation. These results indicate that there is a significant relationship between the level of self-efficacy and burnout of nurses at the Bali Mandara Hospital.